موقف السيد الخميني من القضية الفلسطينية حتى وفاته 1989 (Journal of the College of Basic Education, 2026)
Since the Zionist entity declared the establishment of its state in 1948, positions on that declaration varied between supporters and opponents, and from the first moment, even before the announcement of the so-called (State of Israel), the religious authorities had a clear and explicit position on that declaration, as it was met with rejection, condemnation, and calls for Muslims to defend Palestine. Among the authorities who declared that was Sayyed Ruhollah Khomeini. Since the beginning of his religious and political work, he clearly declared his position rejecting the establishment of the Zionist entity and called for fighting that entity until victory is achieved and Palestine is returned to its liberation. Sayyed did not pay attention to all the forces and institutions that were asking him to stop supporting the Palestinian revolutionary forces, and the support continued publicly after the establishment of the Islamic Republic of Iran in 1979, and much was mentioned in the constitution of the republic about supporting Palestine.